The Development of Taboo Game as Learning Media to Teach Speaking Skill in Eight Grade of Junior High School - Istikomah, Nensi; Saifudin, Ahmad; Mubarok, Tyas Alhim (PROJECT (Professional Journal of English Education), 2025)
This research focuses on developing engaging learning media to teach speaking skills to eighth-grade students at MTs Durriyyatina. Traditional English teaching methods often fail to engage students and encourage active speaking, resulting in limited progress. To address this issue, the study introduces the Taboo game as a language learning tool. The game helps with vocabulary mastery, boosts speaking confidence, and encourages active participation. An R&D approach, including a trial with 24 students, was used to assess the effectiveness of the game. Results showed that the Taboo game significantly improved learning, with a questionnaire score of 89.3%, categorized as very valid. The evaluation indicated that the game is a highly effective teaching medium. This research demonstrates that interactive games like Taboo can enhance students' speaking skills and create a more engaging learning environment. This approach is in line with modern education trends that emphasize interactive, student-centered learning. In conclusion, the Taboo game is an effective solution for teaching speaking skills and increasing student motivation.